2010
DOI: 10.3177/jnsv.56.217
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Nutriture in Newly Diagnosed Diabetes

Abstract: SummaryThis study was performed to investigate the relationship between serum Lascorbic acid, vitamin C intake, and diabetes in a nested case-control study. A cross-sectional survey of diet and health was conducted in 2,048 adults with an age of 30 y or older in Yonchon County, Korea. An oral glucose tolerance test was administered to all participants. One hundred cases of newly diagnosed diabetes were identified. Two healthy controls for each case matched with age, gender, drinking status, and smoking status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(42 reference statements)
1
11
1
Order By: Relevance
“…A lower intake of fruit and vegetables may itself increase the risk of diabetes. Consistent with that, one study found that people with newly diagnosed Type 2 diabetes had lower vitamin C levels than matched healthy controls [9].…”
Section: Diabetes and Vitamin Cmentioning
confidence: 61%
“…A lower intake of fruit and vegetables may itself increase the risk of diabetes. Consistent with that, one study found that people with newly diagnosed Type 2 diabetes had lower vitamin C levels than matched healthy controls [9].…”
Section: Diabetes and Vitamin Cmentioning
confidence: 61%
“…Although, observed benefits in some of our observational studies were related to coadministration of AA and antioxidants (34,41,42,47,52), in majority of studies, single AA was taken (32,36,37,39,40,45,49,53,54). It is thought that the benefits reported in the epidemiological studies in which AA and/or antioxidants are coadministrated, might be related to intake of higher amounts of fruits and vegetables, as a complex mixture of micronutrients or synergistic interaction between natural antioxidants (56).…”
Section: Discussionmentioning
confidence: 85%
“…Association between FBS and AA intake Within 11,471 participants in 14 observational studies (32,33,34,37,40,41,44,45,48,50,53,54,56,57) conducted to assess correlation between FBS and AA intake, 1,148 subjects were diabetics and 610 case were IGT (Impaired glucose tolerance) or IFG (impaired fasting glucose). According to these studies, DM or susceptibility to it presented in 15.32% of participants.…”
Section: Association Between Diabetes and Aa Intake In Observational mentioning
confidence: 99%
“…Plasma vitamin C levels correlate inversely with body mass index and deficiency of vitamin C is reported in 35–45% of obese individuals planning to undergo bariatric surgery [58, 95]. Diabetic patients have lower dietary intake and lower plasma levels of vitamin C than healthy controls [96]. …”
Section: Antioxidant Vitaminsmentioning
confidence: 99%